2005
DOI: 10.1002/jbm.b.30402
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo study of tricalcium phosphate and glutaraldehyde crosslinking gelatin conduits in peripheral nerve repair

Abstract: In order to modulate the mechanical properties of gelatin, we previously developed a biodegradable composite composed by tricalcium phosphate and glutaraldehyde crosslinking gelatin (GTG) feasible for surgical manipulation. In this study, we evaluated the in vivo applications of GTG conduit for peripheral nerve repair. The effect of sciatic nerve reconstruction was compared between resorbable permeable GTG conduits and durable impermeable silicone tubes. Traditional methods of assessing nerve recovery followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
3
22
0
3
Order By: Relevance
“…Similar findings were also observed in a previous study, though these results were limited by extensive swelling and collapse of the biomaterial poly(lactic co-glycolic acid) (PLGA) in the study. CMAP examinations offer an important index for the conduction function of peripheral nerve [2,[28][29][30][31]. In this study, we observed the highest CMAP amplitude of autograft repair in both plantar foot muscles and dorsal muscles.…”
Section: Discussionsupporting
confidence: 58%
“…Similar findings were also observed in a previous study, though these results were limited by extensive swelling and collapse of the biomaterial poly(lactic co-glycolic acid) (PLGA) in the study. CMAP examinations offer an important index for the conduction function of peripheral nerve [2,[28][29][30][31]. In this study, we observed the highest CMAP amplitude of autograft repair in both plantar foot muscles and dorsal muscles.…”
Section: Discussionsupporting
confidence: 58%
“…The nerve conduits prepared from non-degradable biomaterials remain in situ as a foreign body, causing a chronic tissue response, nerve compression, and infection [6,7]. As a result, the nerve guide conduits prepared from biodegradable materials have attracted much more attention [8]. An ideal nerve guide conduit must be biocompatible, biodegradable, soft and flexible, and semipermeable, which can provide a guidance cue via 3D tubular structure, prevent fibrous tissue from ingrowth and meet technical requirements for further production, sterilization, long-term storage and surgical handling [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of a collagen hydrogel aimed at soft tissue repair, it was suggested that calcium phosphate should be included 157 because it has been suggested that Ca 2þ ions are necessary for neurite growth. 158 Thus such ions released from the scaffolds also would improve neurite healing.…”
Section: Blends Of Mineral and Proteinsmentioning
confidence: 99%